1998
DOI: 10.1109/10.678614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoothing window length on electromyogram amplitude estimates

Abstract: A systematic, experimental study of the influence of smoothing window length on the signal-to-noise ratio (SNR) of electromyogram (EMG) amplitude estimates is described. Surface EMG waveforms were sampled during nonfatiguing, constant-force, constant-angle contractions of the biceps or triceps muscles, over the range of 10%-75% maximum voluntary contraction. EMG amplitude estimates were computed with eight different EMG processor schemes using smoothing length durations spanning 2.45-500 ms. An SNR was compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 15 publications
3
21
0
Order By: Relevance
“…Summary measures of sEMG data also vary, depending research objectives (Farfán, Politti, & Felice, 2010;Soderberg & Knutson, 2000). Processing techniques have been shown to influence summary measures of sEMG data (Waly, Asfour, & Kahalil, 1996;St-Amant, Rancour, & Clancy, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Summary measures of sEMG data also vary, depending research objectives (Farfán, Politti, & Felice, 2010;Soderberg & Knutson, 2000). Processing techniques have been shown to influence summary measures of sEMG data (Waly, Asfour, & Kahalil, 1996;St-Amant, Rancour, & Clancy, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Three window lengths were examined: 100, 180, and 250 samples, as these window lengths have been utilized in previous research (Farfán et al, 2010;St-Amant et al, 1998). For each window length, five window overlaps were employed: 0% (i.e., no overlap), 10%, 30%, 50%, and 90%.…”
Section: Exploration Of Rms-processing Parametersmentioning
confidence: 99%
“…Another class of reaching models are stochastic models that take into account the noise inherent to the motor system. It has been consistently observed that the standard deviation of neuromotor commands increases with its mean (Sutton and Sykes 1967;Schmidt et al 1979;Clamman 1969;Matthews 1996;St-Amant et al 1998;Clancy and Hogan 1999;Osu et al 2004). In line with this evidence, it was suggested that the brain minimizes the variance of the final arm position in the presence of such signal-dependent motor noise (Harris and Wolpert 1998;Hamilton et al 2002).…”
Section: Computational Approachmentioning
confidence: 92%
“…Some researchers have applied techniques such as whitening [12,13] or high pass filtering [14] to reduce the variance of the EMG amplitude estimates in force estimation applications.…”
Section: Introductionmentioning
confidence: 99%